Art Therapy and Emotion Regulation Problems Theory and Workbook - Haeyen, Suzanne (Springer International Publishing, 2018)
'Art Therapy and Emotional Regulation Problems' is a "must have" for any art therapist working with service users with emotional dysregulation difficulties. Drawing on proven evidence, Suzanne expertly guides the clinician through a selection of domain specific interventions in a clear and concise manner, making this book, the book I have long been waiting for. Richard Whitaker, Arts Therapies Advisor, Surrey and Borders Partnership NHS Foundation Trust, UK In this innovative work which combines theory and practice, Suzanne Haeyen explores how art therapy can be useful to people with emotion regulation problems, or 'personality disorders', in diagnostic terms. Covering a number of basic themes encountered in clients with personality disorders, it offers insight into the theory behind art therapy techniques and discusses the current state of research in the field. In its second part the author provides a workbook based on aspects of dialectical behavioural therapy skill training developed by Marsha Linehan, including mindfulness, emotion regulation, interpersonal effectiveness and distress tolerance. This section also discusses the use of schema-focused therapy; a method developed by Jeffrey Young, and offers a number of exercises for use in specific practice situations. Alongside summaries of the theory, the author explores the multidisciplinary nature of these therapeutic methods and provides 106 exercises which have been developed in practice. This book offers new ideas and practical tools that will be invaluable to all art therapists working with clients who have difficulties expressing, recognising or coping with their feelings, and who find expressing their feelings through creative work easier than with words. Suzanne Haeyen is an art therapist at the Centre of Expertise for the Treatment of Personality Disorders (Scelta) at GGNet a mental health care centre in the Netherlands. She has worked at the centre since 1991 and chairs its arts therapies and psychomotor therapy section. She is also a senior lecturer at the Arts Therapies education programme of HAN University of Applied Sciences, the Netherlands, and a member of KenVak, a national research centre with a focus on knowledge development for arts therapies.